Modelling crack growth in quasi-brittle materials using mesh fragmentation technique - Maedo, Michael [UNESP]; Manzoli, Osvaldo [UNESP]; Bitencourt, Jr. Luis; Rodrigues, Eduardo; Cardiel, V. C.; Perez, A. S.; Montes, E. H.; Martin, LMG; Pulido, MDG (Univ Sevilla, 2015)
The modelling of discontinuities with new finite element techniques (X-FEM and E-FEM) is cumbersome due to the need of algorithm tracking to simulate the crack growth. Therefore, a new technique to capture strong discontinuities in quasi-brittle materials without the need of a crack tracking scheme is presented. The method consists of inserting solid finite elements with high aspect ratio (ratio of the largest to the smallest dimension) between the bulk elements of the original mesh. Hence, when the ultimate tensile strength is reached only these interface elements are activated. Since the analyses are performed integrally in the context of the continuum mechanics, there is no need to use tracking algorithms to simulate the formation of cracks. The study is performed using different specimens in order to cover the cases that can show up in practice. Numerical results show that the technique is able to represent crack growth.
Keywords: solid finite elements with high aspect ratio; tensile damage model; quasi-brittle materials; crack growth; strong discontinuities